1978
DOI: 10.1002/cne.901790407
|View full text |Cite
|
Sign up to set email alerts
|

The development of the cerebral cortex in the embryonic mouse: An electron microscopic serial section analysis

Abstract: The techniques of reconstructions of cells from serial thin sections and autoradiography after tritiated thymidine injections have been employed to study the early histogenesis of the cerebral cortex in the embryonic day-15 (E15) mouse. The autoradiographic studies show that cells below the E l 5 cortical plate in the intermediate layer are destined to migrate through the preexisting cortical plate cells to take up a more superficial position. Having this information, it has been possible, through reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(149 citation statements)
references
References 59 publications
13
131
0
4
Order By: Relevance
“…This system maintains the architectonic nature of the neocortical wall and is conducive to the study of proliferative kinetics during neocortical growth. The time-lapse procedure elucidated the remarkable and dynamic nature of the embryonic VZ, with all VZ progenitors exhibiting interkinetic movements (3,(29)(30)(31)(32)(33)(34)(35) and cell division simultaneously in each field (see Movies 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…This system maintains the architectonic nature of the neocortical wall and is conducive to the study of proliferative kinetics during neocortical growth. The time-lapse procedure elucidated the remarkable and dynamic nature of the embryonic VZ, with all VZ progenitors exhibiting interkinetic movements (3,(29)(30)(31)(32)(33)(34)(35) and cell division simultaneously in each field (see Movies 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The band of TuJlpositive cells along the ventricular zone-subventricular zone border may restrain the to-and-fro movement of the nuclei, characteristic of the proliferating cells of the ventricular zone (see Takahashi et al, 1993). Another role the TuJ 1 -positive cells may serve, at the border between the ventricular and subventricular zones, is to exclude axons from the ventricular zone (Shoukimas and Hinds, 1978;Edwards et al, 1989). When labeled with DiI, corticothalamic, corticosubcortical, and corticocortical axons never penetrate the ventricular zone of the cerebral cortex and striatum (Menezes and Luskin, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the early steps of this differentiation process have remained elusive. Early autoradiographic and electron microscopic studies (Fujita, 1963;Meller et al, 1966;Hinds and Ruffett, 197 1;Meller and Tetzlaff, 1975;Shoukimas and Hinds, 1978) characterized the ventricular zone as a homogeneous population of asynchronously proliferating cells. To the contrary, in recent years it has been shown that by the onset of cortical neurogenesis distinct glial and neuronal progenitor cells are present within the ventricular zone (Schmechel and Rakic, 1979;Levitt et al, 198 1, 1983;Luskin et al, 1988Luskin et al, , 1993, and that the first appearance of radial glia is an even earlier event (Gressens et al, 1992).…”
Section: Expression Of Neuron-specific Tubulin Defines a Novel Populamentioning
confidence: 99%
“…In other neuronal subpopulations undergoing long-range migration, neuronal morphogenesis undergoes extensive stereotypical changes, leading to polarized outgrowth of their axon and dendrites. This is the case for cerebellar granule neurons (CGN) as well as cortical and hippocampal pyramidal neurons (PN), two of the best-studied models of neuronal polarization (Rakic 1971;Rakic 1972;Shoukimas and Hinds 1978;Gao and Hatten 1993;Komuro et al 2001;Hatanaka and Murakami 2002;Noctor et al 2004). Both CGN and PN acquire their axon -dendrite polarity from the polarized emergence during migration of their trailing and leading processes, respectively (Fig.…”
Section: Axon Initiation In Vivomentioning
confidence: 99%